Ecological Studies on Zooplankton from the Straits of Malacca With Special Reference to Copepods - Rezaei-Marnani, Hamid (2002)
The purpose of this study was to analyze the zooplankton composition and distribution in relation to spatial and temporal variations in the Straits of Malacca. The distribution of zooplankton, was determined using samples collected from 13 to 20 stations during four oceanographic expeditions along the Straits in different periods between 1998 to 2000. Monthly zooplankton samples were also collected from two stations at nearshore and offshore waters off Port Dickson from July 2000 to June 2001. Copepods comprised an average of 71.3%, 71.2%, 70.9% and 57.9% of the total zooplankton populations during consecutive cruises and were the main group of zooplankton during each sampling period. Total zooplankton densities were higher in the near-coastal area than the offshore area. A spatio-temporal variation of zooplankton standing crop both in terms of biomass and density was not significant. Higher mean density estimates of total zooplankton (mean of 12,918 ± 5,635 indo m·3) and that of adult copepods (mean of 2,927 ± 1,085 indo m·3) were recorded during cruise II (pre-SW monsoon) compared to other cruises. However. variation of copepods was temporally insignificant but spatially significant. Higher zooplankton densities were obtained at 10-20 m depth stratum than any other depth strata. Maximum peak of copepod densities collected off Port Dickson waters coincided with NE and pre-SW monsoons when samples were collected horizontally and vertically, respectively. Depth and salinity in associations with other factors explained the distributional patterns of copepods in the studied area. A total of 119 species of pelagic copepods belonging to calanoids (76), cyclopoids (9), harpacticoids (6) and poecilostomatoids (28) were determined during the course of the present investigation. Of these, nine species are new records for the Straits of Malacca. Two characteristic copepod communities in the northern and southern parts of the Straits were distinguished. The shallow southern part was characterised by high-density values and low species diversity (H' = 2.967), and the dominance of few coastal species such as Oithona simplex and Paracalanus parvus. The deeper waters of the northern part were characterised by low-density values, relatively high species diversity index (H' = 3 .632). The heavy metal concentrations in mixed zooplankton were relatively low: ranging from 1.19-1013.70 µg gol wet weight for copper, 1 6.54-235.78 µg gol wet weight for zinc, 3.92-36.08 µg gol wet weight for lead and from 0.32-4.09 µg gol wet weight for cadmium. Concentrations of copper and zinc were higher in near-coastal than offshore areas, whereas those of lead and particularly cadmium were higher in offshore areas